Examination of the Social Emotional Assets and Resilience Scales (SEARS) Youth Report: Factor Structure, Measurement Invariance, and Validity. (October 2022) - Klages, Kimberly L.; Ittenbach, Richard F.; Long, Alanna; Willard, Victoria W.; Phipps, Sean
The Social and Emotional Assets and Resilience Scale (SEARS) is a promising instrument for prediction of resilience in youth; however, there is limited data to support its use. The purpose of the current study was to examine the factor structure, measurement invariance, internal consistency, and validity of the SEARS-Adolescent Report in youth 8 to 20 years of age. Two hundred and twenty-five childhood cancer survivors ( M age = 15.9, SD = 4.2; 51.4% male; 74.5% White) and 122 student controls without history of significant health problems ( M age = 14.2, SD = 3.5; 54.1% female; 79.5% White) 8 to 20 years of age completed the SEARS-A. The SEARS-A was found to have an adequate factor structure and model fit (χ 2 = 1215.5, p < .001; root mean square error of approximation = .057; comparative fit index = .95; standardized root mean square residual = .06) and demonstrated invariance across domains of age, health status, gender, race, and socioeconomic status (Δ comparative fit index < −0.01). It also demonstrated excellent internal reliability, criterion validity, and current validity when compared with another well-established measure of psychological adjustment. As such, the SEARS-A has potential to be a useful, valid, and psychometrically sound tool for predicting social–emotional adjustment outcomes among at-risk youth 8 to 20 years of age.